Symmerty and opposition and their effect on image Composition in the potery of Al-baha Zuhair (Damascus University Journal of arts and humanities sciences, 2024)
This research is based on the formation of the poetic image in the poetry of Al-Baha Zuhair, highlighting the poet’s ability to artistically depict and embody the meanings of his poetry with artistic tools that are harmonious with each other. The poet intended to employ the creative arts, so he used symmetry represented by alliteration - which constitutes a phenomenon for him - and opposition based on antithesis to create images. Poetry that attracts the recipient, influences him, and pushes him to exercise his mind and activate his mind.The poet intensified the semantic function of alliteration. It was not an adornment or adornment, and he was not satisfied with the phonetic aspect and its support for the rhythm. Rather, he worked in many places to form the poetic image, and repetition was supportive of the image and a catalyst for movement in it, and the contrast revealed images that express the tense psychological state that the poet suffers from with the one he loves near and far, love and longing. And connection and separation, or it was a manifestation of the beauty of the beloved, or used in the context of praise.
Keywords: Symmerty; Opposition; Poetic image; Alliteration; Counterpont; Repetition